Penyuluhan Perbedaan Masa Kadaluarsa Obat (ED) dengan Obat Dapat Digunakan Setelah Dibuka (BUD) pada Masyarakat Dusun Kertan Kabupaten Bantul - Shalahuddin Al Madury; Arifah , Mitsalina Fildzah; Aldian , Decky; Maulana, M. Fadlhil Rheza (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2025)
The proper use of drugs is a challenge in society. The level of public knowledge regarding the proper use of drugs is still low. Many people still do not understand the beyond use date (BUD) of semi-solid preparations. BUD is the limit of the drug is still safe and can be used after the packaging is opened, not the same as the Expired date (ED) listed on the drug packaging. So this can cause misunderstanding and is a new thing for the public to know the BUD of a drug preparation. The community service activity on Saturday, October 5, 2024 at 15.30 WIB took place at the Ainun Jariyah Mosque, Kertan Hamlet, Sumberagung, Jetis, Bantul Regency was attended by 31 residents. After pharmacist education was carried out through lectures, and assisted by leaflet media, there was a difference in the number of participants with a moderate pretest level, namely from 6 to 19 people. Education about ED and BUD accompanied by leaflet media can increase public knowledge as seen from the difference in pretest and posttest which shows the number of participants with an increase in correct answers during the pretest and posttest of 68%.